Editorial - Pasierbek, Wit (Horyzonty Wychowania, 2017)
Since 1989 the transformation of the post-communist Europehas been referred to as building civic society in particular countries,connected with regaining independence, recreating a sovereignstate, rebuilding political community and, above all,making the citizen sensitive to responsibility for the society andcommon good. The fifty years of totalitarianism in Poland causedthat the society, to a large degree, lost the sense of responsibilityfor the things which constituted and still constitute commonproperty of the nation many generations. Since the time of politicalchanges, the time has come for a serious reflection uponthe broadly-understood education in the sphere of social life, forconsidering the things which make the society live, as well as itsaspirations and desires. Therefore, we shall also reflect on howthis community perceives its common good and how it wants thisgood to be realised.